Overlapping Functions of the pRb Family in the Regulation of rRNA Synthesis - Ciarmatori, Sonia (American Society for Microbiology, 2001)
The “pocket” proteins pRb, p107, and p130 are a family of negative growth regulators. Previous studies have demonstrated that overexpression of pRb can repress transcription by RNA polymerase (Pol) I. To assess whether pRb performs this role under physiological conditions, we have examined pre-rRNA levels in cells from mice lacking either pRb alone or combinations of the three pocket proteins. Pol I transcription was unaffected in pRb-knockout fibroblasts, but specific disruption of the entire pRb family deregulated rRNA synthesis. Further analysis showed that p130 shares with pRb the ability to repress Pol I transcription, whereas p107 is ineffective in this system. Production of rRNA is abnormally elevated in Rb(−/−) p130(−/−) fibroblasts. Furthermore, overexpression of p130 can inhibit an rRNA promoter both in vitro and in vivo. This reflects an ability of p130 to bind and inactivate the upstream binding factor, UBF. The data imply that rRNA synthesis in living cells is subject to redundant control by endogenous pRb and p130.